SMART GenRe: Sehat Menjaga Reproduksi, Tahu Resiko dan Edukasi pada Remaja - Mawardika, Tina; Umi Aniroh; Agung Wibowo; Alivia Desi Rahmawati; Ahmad Ali Rohman (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2025)
SMK Negeri 2 Salatiga is a vocational high school located in Dukuh Sidomukti, Salatiga, Central Java. A preliminary survey conducted among students revealed that they had never received information related to reproductive health, particularly regarding potential risks and strategies to maintain reproductive organ health. Adolescents are a vulnerable group with respect to reproductive health issues due to limited knowledge, environmental influences, and high curiosity. Insufficient accurate information may lead to risky sexual behavior, unintended pregnancies, sexually transmitted infections (STIs), and psychosocial problems. Evaluation of the activity was carried out using a pre-test and post-test method to measure the improvement of adolescents’ knowledge regarding reproductive health. In addition, observations were conducted to assess participants’ activeness during the educational sessions, and a satisfaction questionnaire was administered to evaluate the effectiveness of the activity and participants’ responses toward the SMART GenRe program. This community service activity aimed to improve adolescents’ knowledge, awareness, and skills in maintaining reproductive health through interactive education and participatory approaches. The program was implemented through health education sessions, group discussions, and case simulations. A total of 59 female students participated in the activity. Prior to the intervention, evaluation results showed that most respondents were in the “poor understanding” category (37.42%), followed by “fair” (26.59%), “good” (28.13%), and “very good” (7.86%). After the intervention, a significant improvement was observed, with the majority of participants categorized as “very good” (35.09%) and “good” (57.07%), while the “fair” category decreased to 6.29% and “poor” to only 1.66%. Based on questionnaire results, it was evident that the educational program improved participants’ understanding of the importance of maintaining reproductive organs, recognizing the risks of sexual behavior, and making healthy and responsible decisions. The overall effectiveness of the intervention was 96.23%. This activity is expected to serve as a sustainable intervention model for preventing adolescent reproductive health problems.   ABSTRAK SMK Negri 2 Salatiga merupakan salah satu Sekolah Menengah Kejuruan yang terletak di Dukuh Sidomukti Salatiga Jawa Tengah. Berdasarkan hasil survey yang telah kami lakukan terhadap mitra yaitu remaja yang bersekolah di SMK tersebut  belum pernah mendapatkan informasi terkait Kesehatan Reproduksi khususnya resiko yang ditimbulkan dan cara menjaga kesehatan organ reproduksi. Remaja merupakan kelompok usia yang rentan terhadap masalah kesehatan reproduksi karena keterbatasan pengetahuan, pengaruh lingkungan, dan rasa ingin tahu yang tinggi. Minimnya informasi yang benar dapat menimbulkan risiko perilaku seksual berisiko, kehamilan tidak diinginkan, infeksi menular seksual (IMS), hingga gangguan psikososial Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan pengetahuan, kesadaran, dan keterampilan remaja dalam menjaga kesehatan reproduksi melalui edukasi interaktif dan pendekatan partisipatif. Evaluasi kegiatan dilakukan dengan metode pre-test dan post-test untuk mengukur peningkatan pengetahuan remaja mengenai kesehatan reproduksi. Selain itu, dilakukan observasi terhadap keaktifan peserta selama sesi edukasi dan pengisian kuesioner kepuasan untuk menilai efektivitas kegiatan dan respon peserta terhadap program SMART GenRe. Metode kegiatan dilakukan dalam bentuk penyuluhan, diskusi kelompok, serta simulasi kasus. Jumlah remaja putri yang mengikuti kegiatan edukasi yaitu 59 responden. Sebelum pelaksanaan edukasi, hasil evaluasi menunjukkan bahwa pemahaman responden masih didominasi kategori kurang paham sebesar 37,42%, diikuti oleh cukup paham 26,59%, pemahaman baik 28,13%, dan sangat baik hanya 7,86%. Setelah intervensi edukasi diberikan, terjadi peningkatan yang cukup signifikan. Mayoritas peserta berada pada kategori sangat baik sebesar 35,09% dan baik sebesar 57,07%, sementara kategori cukup menurun menjadi 6,29% dan kurang tinggal 1,66%. Berdasarkan hasil pengisian kuesioner, diketahui adanya perbaikan pemahaman peserta setelah diberikan edukasi mengenai pentingnya menjaga organ reproduksi, memahami risiko perilaku seksual, serta mampu mengambil keputusan yang sehat dan bertanggung jawab  yang diberikan sebesar 96,23%.  Kegiatan ini diharapkan menjadi model intervensi berkelanjutan dalam upaya pencegahan masalah kesehatan reproduksi remaja.